Exposing and filling the gap in the South African Maternal, Perinatal and Neonatal Health (MPNH) policy in terms of maternal nutrition - Banda, Landilani (University of Pretoria, 2024)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2024.